Still Analyzing the Cartoon Society: Reflecting on The Simpsons for Teaching and Learning Sociology - Scanlan, Stephen; Feinberg, Seth (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
When we wrote "The Cartoon Society: Using The Simpsons to Teach and Learn Sociology" many years back we believed that not only was the show a wonderful snapshot of and commentary on American society but also that this pop culture gem was an excellent means with which to communicate sociological themes and encourage critical thinking among our students. Now many years later, The Simpsons remains a useful tool for teaching a variety of topics central to the discipline, including sociological perspectives on deviance of which Bart Simpson remains a prime purveyor. This essay is a continuation of the essay "The Cartoon Society: Using the the Simpsons to Teach and Learn Society" .